PERLINDUNGAN HUKUM TERHADAP NASABAH BANK PENGGUNA INTERNET BANKING DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Maharani, Silvia; Iswandi, Irvan; Satria , Alfi (Journal of Islamic Studies, 2023)
Advances in information technology, especially internet media, provide many benefits, such as in terms of speed and convenience, but on the other hand, they contain risks that can cause losses to customers. In this regard, protection for customers who use internet banking is needed to protect the rights of customers as consumers of banking services. This study aims to determine the development of internet banking users in Indonesian banking and to determine legal protection for customers who use internet banking from the point of view of laws and Islamic law. The researcher uses a normative juridical approach, namely a legal research method that is carried out by examining library materials. In this study there are primary data sources, namely obtained from laws and regulations, sources of Islamic law and secondary data obtained from articles, bulletins, or scientific papers. Based on the results of the research, it was concluded that although there are no laws and regulations that specifically regulate internet banking, in the positive legal order in Indonesia there are laws that regulate legal protection for consumers (customers who use internet banking), one of which is the establishment of Deposit Guarantee (LPS). Implementation of legal protection for customers who use internet banking by LPS according to Islamic law is permissible, because there is no argument prohibiting its implementation and also the implementation does not contain actions that deviate from the terms and conditions in Islamic law.